Village Financial System Management in Kebumen Regency - Rahmadanti, Mutia; Gamaputra, Gading; Yuni Lestari, Dian Arlupi Utami; Pinata, Putri (KnE Social Sciences, 2022)
The purpose of this study was to examine whether the village financial system in Bocor Village in Bulupspesantren Subdistrict, Kebumen Regency, is suitable for financial management. This was a qualitative descriptive study. The research investigated the village’s financial management, including its planning, implementation, management, reporting, and accountability. Interviews, observations, and document analysis were used to gather information. This study described the village’s financial planning, implementation, management and responsibility, according to Minister of Home Affairs Regulation No. 20 of 2018. According to the results, there were issues with the Village Budget Implementation Report, which was not delivered on time in the first half of 2020. Therefore, the Bocor Village government needs to improve its financial planning discipline to provide more reliable reporting. From the input process to reporting and accountability, Leaky Village has used the village financial system to manage village funds. The timely submission of financial reports should help improve the quality of management in village finances, resulting in more structured and effective village governance. A well-organized village government will benefit the community. Keywords: village finance, village financial system, village financial management